1990
DOI: 10.1038/bjc.1990.209
|View full text |Cite
|
Sign up to set email alerts
|

Systemic cancer and the FAMMM syndrome

Abstract: Summary The FAMMM syndrome consists of the familial occurrence of cutaneous malignant melanoma and atypical nevi (dysplastic nevi), and is inherited as an autosomal dominant trait. Conflicting results have been reported on the question of whether the syndrome includes increased susceptibility to non-melanoma cancers. We have studied cancer of all anatomic sites and histologies in nine FAMMM families which were ascertained in a pigmented lesions clinic in the Netherlands. We evaluated two hypotheses: that the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
3
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 11 publications
5
78
3
1
Order By: Relevance
“…Several studies have demonstrated an increased risk of pancreatic cancer among melanoma-prone families with CDKN2A mutations (Bergman et al, 1990;Goldstein et al, 1995;Bergman and Gruis, 1996;Ghiorzo et al, 1999;Borg et al, 2000;Vasen et al, 2000) but the precise relationship between the CDKN2A gene and pancreatic cancer remains unknown. At present, it is not possible to predict what genotype or phenotype predisposes an individual to pancreatic cancer in these families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated an increased risk of pancreatic cancer among melanoma-prone families with CDKN2A mutations (Bergman et al, 1990;Goldstein et al, 1995;Bergman and Gruis, 1996;Ghiorzo et al, 1999;Borg et al, 2000;Vasen et al, 2000) but the precise relationship between the CDKN2A gene and pancreatic cancer remains unknown. At present, it is not possible to predict what genotype or phenotype predisposes an individual to pancreatic cancer in these families.…”
Section: Discussionmentioning
confidence: 99%
“…Some CDKN2A melanoma-prone families also have pancreatic cancer. Several studies have demonstrated an increased risk of pancreatic cancer among CDKN2A melanoma-prone families (Bergman et al, 1990;Goldstein et al, 1995;Ghiorzo et al, 1999;Borg et al, 2000;Vasen et al, 2000). In addition, germline CDKN2A mutations have been occasionally found in pancreatic cancer patients and families without familial melanoma (Moskaluk et al, 1998;Gerdes et al, 2000;Moore et al, 2000;Lal et al, 2000a;Barsch et al, 2002;Lynch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an increased risk of pancreatic cancer (PC) among CDKN2A melanoma-prone families (10)(11)(12)(13)(14)(15)(16). However, the precise relationship between the CDKN2A gene and PC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Fusaro points out how, in our paper (Ghiorzo et al, 1999), we omitted to mention his report on the association of systemic cancer in familial atypical multiple mole syndrome (FAMMM) (Lynch et al, 1983) and a subsequent study on cancer occurrence in FAMMM kindreds (Bergman et al, 1990) (Kopf et al, 1986;Tucker et al, 1993;Swerdlow et al, 1995;Lynch et al, 1981Lynch et al, , 1983Bergman et al, 1990). These inconsistencies may partly be explained by the reported increased risk of pancreatic cancer in melanoma kindreds with 4 different p16 mutated alleles, including Gly101Trp (Goldstein et al, 1995;Whelan et al, 1995 (Schenk et al, 1998).…”
Section: Reply To Fusaromentioning
confidence: 99%
“…Although the population-based MM cohort identified by Schenk et al (1998) (Boland et al, 1976;Gutman et al, 1991;Wassberg et al, 1996). However, both the Netherlands FAMMM syndrome families (Bergman et al, 1990) and studies on p16 mutated families with early-onset MM and PC (Whelan et al, 1995;Goldstein et al, 1995) (Schenk et al, 1995 …”
Section: Reply To Fusaromentioning
confidence: 99%